Use of room temperature ionic liquids in gas sensor design. - Buzzeo, M; Hardacre, C; Compton, R (2004)
The attainable steady-state limiting currents and time responses of membrane-covered and membrane-independent gas sensors incorporating different electrode and electrolyte materials have been compared. A new design comprising a membrane-free microelectrode modified with a thin layer of a room temperature ionic liquid is considered. While the use of ionic liquid as electrolyte eliminates the need for a membrane and added supporting electrolyte, the slower diffusion of analyte within the more viscous medium results in slower time responses. Such sensors do, however, have potential application in more extreme operating conditions, such as high temperature and pressure, where traditional solvents would volatise.